Ações de enfermagem preventivas de respostas adversas a meio de contraste iodado: uma revisão sistemática - Augusto, Renata Aparecida dos Reis Presses (2022)
The objective of this review was to identify evidence available in the literature on actions of preventive nursing of adverse responses to iodinated contrast media. the question of research for this study was as follows: “What is the effectiveness of preventive nursing actions of adverse reactions developed by patients who will receive iodinated contrast? ”. Method: systematic review based on the recommendations of the Joanna Briggs Institute, the databases consulted were National Library of Medicine and National Institute of Health – PUBMED, Scopus, Cumulative Index to Nursing and Allied Health Literature - CINAHL, Latin American and Caribbean Literature in Health Sciences – LILACS and Scielo. The words keys employed were: contrast media; prevention; nursing care. The criteria study eligibility criteria were primary studies that presented preventive measures with results attributed to the prevention of adverse response to the contrast medium they used methods with the proposal of this review. The identified articles had titles and abstracts analyzed by two different reviewers, who applied the eligibility criteria and selected the articles for full reading. Afterwards, the removal of articles that have not yet met the criteria and the duplicates were analyzed using the software Summarize. Results: From the analysis of the selected articles, the actions of nursing aimed at preventing adverse reactions to iodinated contrast media. At they were grouped into 03 categories, as follows: Assessment of the risk of adverse reactions to the contrast medium, Non-pharmacological measures for the prevention of adverse reactions to the environment of contrast and Specific care with pharmacological measures to prevent reactions adverse to the contrast medium. Conclusion: The evidence from this systematic review resulted in in the organization of nursing actions aimed at preventing adverse responses in the midst of iodinated contrast, in consultations in the various areas of diagnostic support and interventions performed in radiology.